Strategi Peningkatan Pemanfaatan Teknologi Smart Farming di CV Bumi Agro Technology - Gunawan, Stephani; Noor, Trisna Insan (Universitas Galuh, 2026)
Agriculture is a sector with the lowest productivity rate, compared with other sectors in Indonesia. Artificial Intelligence technology usage in the agriculture sector (smart farming) can address the problem, by making the inputs more effective and maximizing the output in agriculture. This research was conducted in CV Bumi Agro Technology, as one of the farms that apply smart farming systems, with the aim to analyze the Technology Readiness Level (TRL) at CV Bumi Agro Technology, and observe applicable strategies to leverage the utilization of smart farming. With qualitative descriptive research methods, the results obtained were the TRL of smart farming in CV Bumi Agro Technology is at level 7 out of 9. The level of conformity in the gap analysis is 77.77%. Strategies that can be applied are doing periodic evaluation regarding the technology, actively collaborating and seeking support, as well as educating and training the manpower.